COMPETENCY CERTIFICATION, TASK COMPLEXITY, MANAGEMENT SUPPORT, AND THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS - Putu Devi Armaviliani; Ni Luh Sari Widhiyani (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The accounting information system (AIS) plays a crucial role in supporting the processes of collecting, recording, processing, and reporting reliable and timely accounting information. The effectiveness of AIS is essential for organizations, including cooperatives, in enhancing operational efficiency, producing quality information for decision-making, and ensuring accurate financial data recording. This study aims to obtain empirical evidence on the effect of competency certification, task complexity, and management support on the effectiveness of accounting information systems. The sample was selected using a non-probability purposive sampling method, involving 80 respondents. Data analysis was conducted using multiple linear regression analysis. The findings indicate that competency certification, task complexity, and management support have a positive effect on AIS effectiveness. These results also suggest that the more certifications obtained, the higher the task complexity and management support, the greater the effectiveness of AIS. The theoretical implication of this study supports the application of the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) in empirical research on AIS effectiveness.